Morphological and biochemical characterisation of sensory neurons infected in vitro with rabies virus (2007)
This work was aimed at the morphological and biochemical characterisation of the most susceptible neuronal subpopulation to rabies virus (RABV) infection. Adult mouse DRG cultures were infected with RABV and double-processed for viral antigen detection and neuropeptides: calcitonine gene-related peptide (CGRP), galanin (GAL), substance P (SP), neuropeptide Y (NPY) and vasoactive intestinal peptide (VIP). It was found that 56% of the neurons in culture were small (diameter <20 m) but, in spite of this, 69% of the infected neurons had intermediate and large diameters (̧20 m). More than 50% of infected neurons expressed NPY, VIP or SP, whereas no association was found between infected neurons and the presence of CGRP or GAL. Despite SP having been shown to be a small neuron marker, it was found that RABV infects medium and large-sized SP positive cells. RABV preference for larger neurons could explain part of the neuropathogenesis since it can be suggested that, following a rabid accident, the virus uses large neurons (mainly innervating muscle and joints) in vivo to be transported later on to the central nervous system.